2-Methylbutyl acetate in wines: Enantiomeric distribution and sensory impact on red wine fruity aroma. (15th December 2017) - Cameleyre, Margaux; Lytra, Georgia; Tempere, Sophie; Barbe, Jean-Christophe
Highlights: Only the (S)-2-Methylbutyl acetate enantiomer was detected in red and white wines. Concentrations were higher in red than white wines. (S)-2-Methylbutyl acetate was presented at sub-threshold concentrations. (S)-2-Methylbutyl acetate was a natural enhancer of fruity notes. Abstract: Enantiomers of 2-methylbutyl acetate were assayed in red and white commercial wines from various vintages and origins, using chiral gas chromatography (γ-cyclodextrin), revealing the exclusive presence of the S-enantiomeric form. Results also confirmed that (S)-2-methylbutyl acetate levels were generally higher in red than white wines of the same age, and that acetate levels increased gradually during ageing. Olfactory threshold of (S)-2-methylbutyl acetate was evaluated at 313 µg/L in dilute alcohol solution (12% v/v) and 1083 µg/L in a fruity aromatic reconstitution, reflecting its presence in wines at subthreshold concentrations. At concentrations considerably lower than its olfactory threshold, 2-methylbutyl acetate was associated with blackberry-fruit and banana notes. It was also revealed that, even at subthreshold concentrations, this compound had a modification on the perception of fruity aromas in the matrices studied. Sensory profiles highlighted, for the first time, its specific contribution to black-, fresh-, and jammy-fruit notes, despite its subthreshold concentrations.